SWEET POTATO: A PROMISING CROP FOR FOOD SECURITY AND FORAGE - Ковтун, Олена; Стюрко, Марина; Андрушко, Олег; Андрушко, Микола (SWorldJournal, 2024)
The article provides a brief overview of the state of sweet potato crop production in the world. Analysis of primary sources indicates the importance of this culture in solving the global food crisis and solving food security problems related to climate c